Arctic Ocean temperatures - Maric, Filip; Poto, Margherita Paola; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Focus: To understand what water temperature is, and why it is important for life in the ocean. What factors influence water temperature (e.g., sunlight, solar radiation, heat transfer)? Learning objectives: In this activity, pupils will learn that temperature is an important factor influencing water, water quality, and altering the physical and chemical properties of water. Key words: Temperature, solar radiation, heat transfer, changes & drivers, consequences.